Duration of forensic psychiatric care and subsequent criminal recidivism in individuals sentenced in Sweden between 2009 and 2019 - Sivak, Lenka; Forsman, Jonas; Masterman, Thomas (Frontiers in Psychiatry, 2023)
Background The duration of forensic psychiatric care is in Sweden not determined at the time of sentencing; instead, offenders are regularly evaluated, often with regard to risk of criminal recidivism. The length and justifiability of such a sanction have been greatly debated; however, previous estimates of treatment duration – based on datasets delimited to discharged patients – have provided an uncertain groundwork for these deliberations. The aim of this study was to use a more suitable approach to calculate average duration of forensic psychiatric care and to examine the relationship between length of treatment and subsequent recidivism after discharge. Methods This retrospective cohort study focused on offenders sentenced to forensic psychiatric care in Sweden between 2009 and 2019 and registered in the Swedish National Forensic Psychiatric Register (n=2064), with a follow-up period until May 2020. We used Kaplan-Meier estimator to calculate and visualize treatment duration including analyses comparing levels of relevant variables, and then evaluated criminal recidivism in patients discharged from treatment between 2009 and 2019 (n=640), after stratification for the same variables and dichotomization by treatment duration. Results The median duration of forensic psychiatric care was estimated to 89.7 months (95% CI 83.2-95.8). Treatment was longer in offenders who committed violent crimes, suffered from psychosis or had a history of substance use disorder, and in offenders whose sentences included special court supervision. The cumulative incidence of recidivism in patients discharged from treatment was estimated to 13.5% at 12 months (95% CI 10.6-16.2) and 19.5% at 24 months (95% CI 16.0-22.8). Corresponding cumulative incidence of violent crime post discharge was 6.3% at 12 months (95% CI 4.3-8.3) and 9.9% at 24 months (95% CI 7.3-12.4). Among other findings, in patients without a history of substance use disorder and patients whose sentences did not include special court supervision, recidivism was significantly higher in those with a shorter treatment duration. Conclusion Using the entirety of a suitable, contemporary, prospectively enrolled cohort of mentally ill offenders, we were able to estimate – with greater accuracy than previous studies – the average duration of Swedish forensic psychiatric care and rate of subsequent criminal recidivism.